Managers' Overconfidence, Risk Preference, Herd Behavior and Non-efficient Investment - Yi, Huang (2019)
With the bounded rationality hypothesis, the psychological deviation of managers often leads to non-efficient investment decision-making practices. The study examines the impact of manager’s overconfidence, risk-preference and herd behavior on non-efficient investment using the Chinese A-shares listed company data as the research object, and finds that: (1) managers’ overconfidence and herd behavior would lead to more non-efficient investment in Chinese listed companies; and (2) managers’ risk preference restrains the increase of non-efficient investment to some extent. Meanwhile, the influence of the manager’s psychological deviation on the actual investment decision is a complicated process and can have a comprehensive effect resulted from the interaction of the above psychological biases, we also find that (3) managers' overconfidence is an interactive term in the effects of herd behavior and risk preference on non-efficient investment. That is, managers’ overconfidence can significantly reduce the positive effect of herd behavior on non-efficient investment; and can also significantly relieve the inhibition effect of risk preference on non-efficient investment. These findings reveal that it is important to understand managers’ irrational behaviors in enterprise investment decision-makings.